Worldwide evidence of a unimodal relationship between productivity and plant species richness - Fraser, Lauchlan H. (2015)
The search for predictions of species diversity across environmental gradients haschallenged ecologists for decades. The humped-back model (HBM) suggests that plantdiversity peaks at intermediate productivity; at low productivity few species can toleratethe environmental stresses, and at high productivity a few highly competitive speciesdominate. Over time the HBM has become increasingly controversial, and recent studiesclaim to have refuted it. Here, by using data from coordinated surveys conductedthroughout grasslands worldwide and comprising a wide range of site productivities, weprovide evidence in support of the HBM pattern at both global and regional extents. Therelationships described here provide a foundation for further research into the local,landscape, and historical factors that maintain biodiversity.